2020
DOI: 10.1093/cercor/bhz334
|View full text |Cite|
|
Sign up to set email alerts
|

Synaptic Mechanisms Underlying the Network State-Dependent Recruitment of VIP-Expressing Interneurons in the CA1 Hippocampus

Abstract: Disinhibition is a widespread circuit mechanism for information selection and transfer. In the hippocampus, disinhibition of principal cells is provided by the interneuron-specific interneurons that express the vasoactive intestinal polypeptide (VIP-IS) and innervate selectively inhibitory interneurons. By combining optophysiological experiments with computational models, we determined the impact of synaptic inputs onto the network state-dependent recruitment of VIP-IS cells. We found that VIP-IS cells fire sp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
63
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 43 publications
(69 citation statements)
references
References 85 publications
3
63
0
Order By: Relevance
“…Interestingly, GABAergic septohippocampal innervation of CA1 CR+ interneurons is decreased during aging ( Rubio et al, 2012 ). Thus, changes in the spontaneous inhibitory tone observed in our study may reflect increased activity of local inhibitory interneurons contacting I-S3 cells, such as other VIP+ and CR+ interneurons ( Luo et al, 2020 ). Furthermore, while I-S3 cells receive excitatory input from the CA3 area ( Luo et al, 2020 ), which can become hyperactive in old rodents ( El-Hayek et al, 2013 ; Simkin et al, 2015 ), we have not observed any sign of hyperactivity or seizure-like excitatory patterns arriving to I-S3 cells from this region.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Interestingly, GABAergic septohippocampal innervation of CA1 CR+ interneurons is decreased during aging ( Rubio et al, 2012 ). Thus, changes in the spontaneous inhibitory tone observed in our study may reflect increased activity of local inhibitory interneurons contacting I-S3 cells, such as other VIP+ and CR+ interneurons ( Luo et al, 2020 ). Furthermore, while I-S3 cells receive excitatory input from the CA3 area ( Luo et al, 2020 ), which can become hyperactive in old rodents ( El-Hayek et al, 2013 ; Simkin et al, 2015 ), we have not observed any sign of hyperactivity or seizure-like excitatory patterns arriving to I-S3 cells from this region.…”
Section: Discussionmentioning
confidence: 79%
“…Importantly, aging is associated with deficits in the theta oscillation power resulting in the impaired encoding of novel spatial information in the dorsal hippocampus or emotional states in the ventral hippocampus ( Jacobson et al, 2013 ). Modeling data combined with imaging in vivo of I-S3 cell activity in awake mice indicated that I-S3 cells are recruited during theta oscillations ( Luo et al, 2020 ) and may play a role in modulating the activity of O-LM cells at theta frequency ( Tyan et al, 2014 ). Indeed, in young animals, optogenetic activation of CR+ cells increased the post-inhibitory firing of O-LM cells specifically at theta frequency ( Tyan et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Note that this number of PYR cell inputs is fixed across simulations. The times at which the 3 PYR cell inputs are activated are indicated by the yellow arrows and start with a delay of 78.125 ms relative to I-S3 cell inputs, consistent with their relative timing during theta rhythms (4, 16). C: Example synaptic locations (left) of 30 PYR cell inputs onto an OLM cell model.…”
Section: Methodsmentioning
confidence: 73%
“…Importantly, I-S3 cell inputs are a major source of inhibitory synaptic inputs to OLM cells (13) . Overall, these model developments provide an opportunity to do a detailed in silico exploration of the potential contributions of I-S3 cells in a behaving animal via its control over OLM cells during theta activities, given all of our previous findings on OLM cell dendritic h-channels (27, 31), advancements in generating detailed in vivo virtual network simulations (32, 33), and discovery of the activation patterns of I-S3 cells during animal behaviour (16).…”
Section: Introductionmentioning
confidence: 99%
“…Further, we have now used the current OLM cell models to do detailed, dendritic explorations of ion channel dynamics that would not be possible to do experimentally (Guet-McCreight and Skinner, 2020 ). We have also created in vivo -like states with interneuron-specific interneuron models (Guet-McCreight and Skinner, 2019 ), and used them to make links between in vitro and in vivo studies (Luo et al, 2020 ). In essence, it seems possible that an understanding of the contribution of biophysical cellular details to circuits in the behaving animal can emerge by using virtual networks.…”
Section: Discussionmentioning
confidence: 99%